1970
DOI: 10.1093/genetics/65.4.585
|View full text |Cite
|
Sign up to set email alerts
|

THE MECHANISM OF SOMATIC ASSOCIATION IN COMMON WHEAT, TRITICUM AESTIVUM L. II. DIFFERENTIAL AFFINITY FOR COLCHICINE OF SPINDLE MICROTUBULES OF PLANTS HAVING DIFFERENT DOSES OF THE SOMATIC-ASSOCIATION SUPPRESSOR

Abstract: HE homologous chromosomes of common wheat, Triticum crestiuum L., are Tassociated in somatic cells (FELDMAN, MELLO-SAMPAYO and SEARS 1966). This somatic association is regulated by a gene system located on the chromosomes of homoeologous group 5, i.e., chromosomes 5A, 5B, and 5D, (FELDMAN 1966(FELDMAN , 1968). The long arm of chromosome 5B (5BL) carries a gene which SUPpresses somatic association and thus tends to cause random distribution of homologues in the somatic nucleus. On the other hand, the short arm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…This situation is said to prevail in the presence of the gene on chromosome 5B which is associated with normal bivalent pairing in wheat, but not in its absence (where multivalent pairing is expected at meiosis). It has also been reported that this gene on chromosome 5B alters spindle tubulin (Avivi, Feldman & Bushuk 1970). Such findings seem consistent with the interpretation that each of the three wheat genomes may have a specific centromere relationship to a special spindle or spindle region of its own and that a normal chromosome 5B gene is needed for the maintenance of the relation ship.…”
Section: Comparisons Offrequencies O F Pachytene Synapsis and Crossing Over In Materials Heterozygous For Rearranged Chromosome Segmentssupporting
confidence: 84%
“…This situation is said to prevail in the presence of the gene on chromosome 5B which is associated with normal bivalent pairing in wheat, but not in its absence (where multivalent pairing is expected at meiosis). It has also been reported that this gene on chromosome 5B alters spindle tubulin (Avivi, Feldman & Bushuk 1970). Such findings seem consistent with the interpretation that each of the three wheat genomes may have a specific centromere relationship to a special spindle or spindle region of its own and that a normal chromosome 5B gene is needed for the maintenance of the relation ship.…”
Section: Comparisons Offrequencies O F Pachytene Synapsis and Crossing Over In Materials Heterozygous For Rearranged Chromosome Segmentssupporting
confidence: 84%